Human eosinophil granulocytes do not express the enzyme arginase - Luckner-Minden, Claudia; Fischer, Ina; Langhans, Claus-Dieter; Schiller, Martin; Kropf, Pascale; Müller, Ingrid; Hohlfeld, Jens M; Ho, Anthony Dick; Munder, Markus (Journal of leukocyte biology, 2010)
Human eosinophils lack the mechanism of arginase-mediated arginine depletion as a key immunosuppressive mechanism of neutrophil granulocytes.Human polymorphonuclear PMN constitutively express the enzyme arginase I, which hydrolyzes arginine to ornithine and urea. This arginine consumption has been recognized as a key pathway of myeloid cell-mediated suppression of the adaptive immune system during inflammation, infection, and tumor growth. Eos granulocytes are crucial immunoregulatory and effector cells of allergic inflammation and infections with parasites and helminths and in a variety of tumors. Here, we analyzed if human Eos also express arginase with its potential immunosuppressive consequences. We show that human peripheral blood Eos do not express arginase I or II protein or arginase enzymatic activity. Correspondingly, no metabolism of arginine to ornithine can be detected in Eos-S. Neither Eos apoptosis nor cytokine-mediated cellular activation induces arginase in human Eos in vitro. Finally, we show that arginase activity and protein are also undetectable in Eos of allergic patients from peripheral blood or from BALF activated in vivo during allergic pulmonary inflammation. This work demonstrates a fundamental difference between neutrophil and Eos granulocytes. As Eos are not equipped with the immunosuppressive enzyme arginase, they cannot participate, via arginine limitation, in the suppression of the evolving adaptive immune response in allergy, infections, or tumor immunity.
Gesehen am 19.04.2023